The fungus gnats (Diptera: Bolitophilidae, Keroplatidae, Mycetophilidae) of Sardinia, with description of six new species - Chandler, Peter J. (Zootaxa, 2009)
The fungus gnat fauna of Sardinia is reviewed and data presented for all species recorded. Altogether one species of Bolitophilidae, 16 species of Keroplatidae and 105 species of Mycetophilidae are recognised as occurring in Sardinia. As the bolitophilid and two of the mycetophilid species are represented only by females and are not determined to species level, the total confirmed Sardinian list stands at 119 species. Four species of Keroplatidae and 19 species of Mycetophilidae are new to the total Italian fauna, whereas three species of Keroplatidae and 32 species of Mycetophilidae are newly recorded for the island of Sardinia. Six species are described as new to science: two Keroplatidae (Urytalpa juliae sp. nov., Macrocera nuragica sp. nov.) and four Mycetophilidae (Boletina ichnusa sp. nov., Trichonta sandalyon sp. nov., Sciophila benjaminbottomi sp. nov., Sciophila immodesta sp. nov.). The new synonymy Zygomyia valida Winnertz, 1863 = Zygomyia simplex Strobl, 1895 syn. nov. is established. Macrocera penicillata Costa, 1857 is tentatively considered as a synonym of M. phalerata Meigen, 1818. Label data are provided for 5 and 17 species recorded without further detail in the Fauna Europaea online database, respectively from Italian mainland and Sicily; one species, Mycetophila alea Laffoon, 1965 is newly recorded for Sicily. Three species based onunconfirmed 19 th century records cited by Hellrigl from South Tyrol should be deleted from the Italian list: Exechiopsis indecisa (Walker, 1856), Mycetophila signata Meigen, 1830 and Mycomya storai Väisänen, 1979.